Predicting Anxiety and Depression in Adolescents with Autism Spectrum Disorder Based on Childhood Trauma Severity: The Mediating Role of Emotion Regulation Difficulties - Samadi, Farshad; Khoshakhlagh, Maedeh; yazdani, Melika (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: The aim of this study was to investigate the mediating role of emotion regulation difficulties in the relationship between childhood trauma and symptoms of anxiety and depression in adolescents with ASD. Methods and Materials: This study employed a descriptive-correlational design using a cross-sectional approach. The research sample consisted of 200 adolescents aged 12 to 18 years with ASD, who were selected through convenience sampling from rehabilitation centers in Tehran during the 2024–2025 academic year. The instruments used included the Childhood Trauma Questionnaire (CTQ), the Difficulties in Emotion Regulation Scale (DERS), and the Revised Child Anxiety and Depression Scale (RCADS). Data were analyzed using structural equation modeling (SEM) via AMOS-24 software. Findings: The results indicated that childhood trauma was directly associated with symptoms of anxiety and depression. Moreover, emotion regulation difficulties significantly mediated the relationship between childhood trauma and both psychological variables. The model fit indices demonstrated acceptable levels of fit. Conclusion: The findings highlight the significance of emotion regulation as a key mechanism in explaining the adverse effects of childhood trauma on the mental health of adolescents with ASD. Interventions aimed at enhancing emotion regulation may be effective in reducing anxiety and depression symptoms in this population.